Pemanfaatan Teknologi Pratanak dalam Pemberdayaan Petani dan Pedagang Beras di Kabupaten Takalar, Sulawesi Selatan - Rahman, Andi Nur Faidah; Jalaluddin, Jalaluddin; Tahir, Mulyati Muhammad; Langkong, Jumriah (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Takalar Regency is a region in South Sulawesi Province where rice is the leading agricultural commodity, surpassing other crops such as corn, tubers, and legumes. Along with the rising incidence of degenerative diseases particularly diabetes mellitus (DM), which is suspected to be linked to excessive consumption of high glycemic rice public awareness of choosing healthier rice options has increased. One of the innovations currently being developed to address this issue is parboiling technology, which can reduce the glycemic index (GI) of rice. In addition to its health benefits, parboiled rice also holds high economic value and has the potential to empower local rice farmers and traders. This activity aimed to educate the community on the benefits of consuming parboiled rice and to provide hands-on training in its production. The method used involved both counseling and practical training sessions, conducted in Tala Village, Sombalabella Subdistrict, Pattalassang District, Takalar Regency. The participants consisted of 40 women who are farmers and rice traders, economically unproductive at the time. The program was delivered in two sessions: a material presentation and practical training. Based on the participants’ questionnaire responses, knowledge about parboiled rice increased significantly from only 47% awareness before the activity to 100% afterward. In terms of skills, none of the participants initially knew how to make parboiled rice, but after the training, 90% were able to do it independently. The conclusion of this activity is that the counseling and training on the utilization of parboiling technology can broaden the community's knowledge and enhance their skills in producing parboiled rice.